2010
DOI: 10.1097/nna.0b013e3181ee4248
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Technology Supports Bedside Documentation

Abstract: As the conversion to an electronic health record intensifies, the question of which data-entry device works best in what environment and situation is paramount. Specifically, what is the best mix of equipment to purchase and install on clinical units based on staff preferences and budget constraints? The authors discuss their evaluation of stationary personal computers, workshops on wheels, and handheld tablets related to timeliness of data entry and their use of focus groups to ascertain the pros/cons of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Ward et al studied the effect of the transition from paper-based emergency care records to EHR and found that there are problems with time stamps of the data [ 28 ], and further a study on blood pressure measurement registrations in emergency departments also indicated problems with currency [ 36 ]. If the systems used for documentation are not available to the staff at the point of care registrations will be delayed [ 37 , 38 ]. We would argue that the point of care documentation concept would need to include mobility as patients and staff in a busy emergency department are on the move.…”
Section: Discussionmentioning
confidence: 99%
“…Ward et al studied the effect of the transition from paper-based emergency care records to EHR and found that there are problems with time stamps of the data [ 28 ], and further a study on blood pressure measurement registrations in emergency departments also indicated problems with currency [ 36 ]. If the systems used for documentation are not available to the staff at the point of care registrations will be delayed [ 37 , 38 ]. We would argue that the point of care documentation concept would need to include mobility as patients and staff in a busy emergency department are on the move.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the laptop, mobile devices and suitable applications offer exciting potential not only to facilitate clinical workflow, but to enable patients and families to engage in their healthcare in ways that are integrated into their daily lives [58,59]. Significant benefits will be realized in the inpatient setting where providers are responsible for multiple patients in disparate locations; however, it is expected that mobile applications will allow ambulatory practitioners to complete sequential tasks efficiently as well.…”
Section: Mobile Devices and Applicationsmentioning
confidence: 99%
“…In this case, the nursing division of a large tertiary -quaternary Australian health service conceived of a modular, electronic audit tool to allow data collection at the bedside. Data collection at the bedside using a range of devices is a topic of interest amongst nursing staff given the nature of their work [13]. In this case, the senior nursing staff had a vision of a system that would dramatically improve the efficiency and validity of the audit process, as well as of resultant intelligence about care that could improve outcomes for patients in a range of dimensions.…”
Section: Introductionmentioning
confidence: 99%